Taking the EZ way: Targeting enhancer of zeste homolog 2 in B-cell lymphomas. (November 2022) - Morschhauser, Franck; Salles, Gilles; Batlevi, Connie Lee; Tilly, Hervé; Chaidos, Aristeidis; Phillips, Tycel; Burke, John; Melnick, Ari
Abstract: Enhancer of zeste homolog 2 (EZH2) is an epigenetic regulator that controls the normal biology of germinal B cells. Overexpression or mutation of EZH2 is associated with malignant transformation in a number of B-cell malignancies; thus, EZH2 inhibitors are an attractive therapeutic option for these targets. Several EZH2 inhibitors have entered clinical trials, but there remains an important question as to how EZH2 inhibitor mechanism of action differs in patients with mutant and wild-type EZH2 . This review discusses the EZH2-driven mechanisms that lead to the development of B-cell lymphomas and act as therapeutic targets. Another key area of investigation is whether EZH2 inhibitors will work synergistically with existing immunomodulatory drugs and chemotherapy regimens. In summary, EZH2 inhibitors show potential as treatment for a range of B-cell lymphomas, and numerous clinical evaluations are currently underway. Highlights: Both wild-type and mutant EZH2 contribute to lymphomagenesis. EZH2 inhibitors are promising agents for the treatment of B-cell lymphomas. Preclinical and clinical data show favorable tolerability of EZH2 inhibitors. EZH2 inhibitors are effective in combination therapy regimens.